Intranasal Insulin Prevents Anesthesia-Induced Cognitive Impairment and Chronic Neurobehavioral Changes - Chen, Yanxing; Dai, Chun-Ling; Wu, Zhe; Iqbal, Khalid; Liu, Fei; Zhang, Baorong; Gong, Cheng-Xin (Frontiers in Aging Neuroscience, 2017)
General anesthesia increases the risk for cognitive impairment post operation, especially in the elderly and vulnerable individuals. Recent animal studies on the impact of anesthesia on postoperative cognitive impairment have provided some valuable insights, but much remains to be understood. Here, by using mice of various ages and conditions, we found that anesthesia with propofol and sevoflurane caused significant deficits in spatial learning and memory, as tested using Morris Water Maze (MWM) 2–6 days after anesthesia exposure, in aged (17–18 months old) wild-type (WT) mice and in adult (7–8 months old) 3xTg-AD mice (a triple transgenic mouse model of Alzheimer’s disease (AD)), but not in adult WT mice. Anesthesia resulted in long-term neurobehavioral changes in the fear conditioning task carried out 65 days after exposure to anesthesia in 3xTg-AD mice. Importantly, daily intranasal administration of insulin (1.75 U/mouse/day) for only 3 days prior to anesthesia completely prevented the anesthesia-induced deficits in spatial learning and memory and the long-term neurobehavioral changes tested 65 days after exposure to anesthesia in 3xTg-AD mice. These results indicate that aging and AD-like brain pathology increase the vulnerability to cognitive impairment after anesthesia and that intranasal treatment with insulin can prevent anesthesia-induced cognitive impairment.